Are there export spillovers in manufacturing industry? Evidence from Switzerland. (22nd August 2019) - Hamida, Lamia Ben; Ischer, Patrick
Apart from foreign direct investment (FDI), multinationals' (MNCs) export activities are also a valuable source of knowledge for domestic firms (in the home and the host countries). The aim of this paper is to focus in detail on the role of MNCs' export activities in improving the export performance of domestic firms through export spillovers. In particular, we test whether export activities of both Swiss and foreign MNCs located in Switzerland may benefit the Swiss economy when the export specific knowledge that is experienced on foreign markets may spill over to domestic firms, raising their export propensity. We argue that export spillovers do not occur automatically. They depend upon the mechanism by which they take place, the absorptive capacity of domestic firms, the export destination, and the geographical proximity. We found that the probability that domestic firms exports is positively and significantly associated with the presence of MNCs exporters in their sector. Demonstration-imitation is the main mechanism for these benefits. These benefits are larger when specific by destination and when domestic firms are in close proximity to foreign and Swiss MNCs. In addition, domestic firms with high technological capacities benefit more from export spillovers.